Antioxidant and antimicrobial activities of mango peel and radish peel-a comparative investigation - Koirala, Pankaj; Chunhavacharatorn, Phatchada; Suttisansanee, Uthaiwan; Benjakul, Soottawat; Katewongsa, Kanlaya; Al-Asmari, Fahad; Nirmal, Nilesh (Frontiers in Sustainable Food Systems, 2024)
The present study investigated the antioxidant and antimicrobial activities of Bao mango and daikon radish peel (Thai variety) ethanolic extracts. The percentage extraction yield of radish peel was higher compared to the mango peel (P< 0.05). However, Mango peel extract (MPE) contained higher total phenolic content (TPC) than radish peel extract (RPE) (P< 0.05). Similar to the TPC value, antioxidant activities including DPPH radical scavenging activity, reducing power, and peroxidation inhibition were higher in the MPE, compared to the RPE, except for metal chelating activity. The antimicrobial analyses suggested that the MPE showed lower minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values compared to the RPE (P<0.05) against Gram-positive and Gram-negative bacteria.High-performance liquid chromatography (HPLC) revealed that mangiferin was the major phenolic compound present in MPE, followed by 3, 4 dihydroxybenzoic acid. Therefore, MP could be used as a promising natural antioxidant and antimicrobial agent for food applications.